(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The purpose of this study is to assess the knowledge, attitude, perception and to create awareness regarding Benign prostatic hyperplasia and prostate cancer among men older than 40 years. Objectives: To determine the perception and understanding regarding benign prostatic hyperplasia and prostate cancer among men older than 40 years of age. To provide information regarding benign prostatic hyperplasia and prostate cancer. Study design: This study is design as a online cross sectional study. Study Duration: The study will be carried from the month of August (2021) to April (2022) – 9 months. Study Instruments: The study instrument is developed and carried out with the use of self-developed questionnaire after a thorough literature analysis which will be assessed and validated by Physicians. Statistical Analysis: Microsoft sheet and SPSS software version 24 will be used for statistical analysis of the data. Descriptive analysis of quantitative variables will be done by using mean, standard deviation, and Chi-square test. Conclusion: The results of this study suggest that the men population in Chennai lack knowledge regarding prostate disease. This study recommends widespread public health campaigns using the mass media, hospitals, and religious centres to improve knowledge, attitude and screening practices regarding prostatic diseases.